Bacteriophage transfer during faecal microbiota transplantation in Clostridium difficile infection is associated with treatment outcome. Issue 4 (24th May 2017) - Zuo, Tao; Wong, Sunny H; Lam, Kelvin; Lui, Rashid; Cheung, Kitty; Tang, Whitney; Ching, Jessica Y L; Chan, Paul K S; Chan, Martin C W; Wu, Justin C Y; Chan, Francis K L; Yu, Jun; et al.
Abstract : Objective: Faecal microbiota transplantation (FMT) is effective for the treatment of recurrent Clostridium difficile infection (CDI). Studies have shown bacterial colonisation after FMT, but data on viral alterations in CDI are scarce. We investigated enteric virome alterations in CDI and the association between viral transfer and clinical outcome in patients with CDI. Design: Ultra-deep metagenomic sequencing of virus-like particle preparations and bacterial 16S rRNA sequencing were performed on stool samples from 24 subjects with CDI and 20 healthy controls. We longitudinally assessed the virome and bacterial microbiome changes in nine CDI subjects treated with FMT and five treated with vancomycin. Enteric virome alterations were assessed in association with treatment response. Results: Subjects with CDI demonstrated a significantly higher abundance of bacteriophage Caudovirales and a lower Caudovirales diversity, richness and evenness compared with healthy household controls. Significant correlations were observed between bacterial families Proteobacteria, Actinobacteria and Caudovirales taxa in CDI. FMT treatment resulted in a significant decrease in the abundance of Caudovirales in CDI. Cure after FMT was observed when donor-derived Caudovirales contigs occupied a larger fraction of the enteric virome in the recipients (p=0.024). In treatment responders, FMT was associated with alterations in the virome and the bacterial microbiome, while vancomycin treatment led to alterations in the bacterial community alone. Conclusions: In a preliminary study, CDI is characterised by enteric virome dysbiosis. Treatment response in FMT was associated with a high colonisation level of donor-derived Caudovirales taxa in the recipient. Caudovirales bacteriophages may play a role in the efficacy of FMT in CDI. Trial registration number: NCT02570477